Power and Persuasion : Fiestas and Social Control in Rural Mexico - Brandes, Stanley H. (Book collections on Project MUSE., 1988)
Demonstrates how the annual fiesta cycle reflects political dependency of local communities on the nation-state, helps maintain formal authority, and perpetuates behavioral norms and social values.